Efficient Transfer of the Medium Frequency Magnetic Field Using Anisotropic Metamaterials - Adam Steckiewicz (Energies, 2022)
This paper introduces a novel waveguide intended for the spatial transfer of alternating magnetic fields. Instead of ferromagnetic material, an air core was proposed, while the cladding was realized using anisotropic metamaterial, built of the resonators and a paramagnetic composite. Since prior works regarding magnetic field transfer concentrated on static or high frequency fields, the proposed device complements the range of medium frequencies (several to hundreds of kilohertz). The three-dimensional model of the 50 cm long and 20 cm wide rectangular structure with metamaterial cladding was made in COMSOL and computed using the finite element method. Multi-turn inductors were considered and homogenized by the current sheet approximation, while an optimization solver was used to identify an optimal design of the waveguide. The analysis was made with respect to different resonators and permeability of the paramagnetic material. Additionally, the frequency response of the structure was determined. On these bases, the dependencies of the mean energy density and magnetic field intensity at the output of the waveguide were characterized. It was shown that discussed structure was able to provide an efficient transfer of the magnetic field between two ports. Thus, this device can be used to extend the distance of the wireless power transfer, especially between devices isolated by a thick barrier (e.g., wall), in which the meta-structure may be embodied.